Early uptake of HIV counseling and testing among pregnant women at different levels of health facilities - experiences from a community-based study in Northern Vietnam - Gammeltoft Tine; Hạnh Nguyễn; Rasch Vibeke (BMC, 2011)
Abstract Background HIV counselling and testing for pregnant women is a key factor for successful prevention of mother to child transmission of HIV. Women's access to testing can be improved by scaling up the distribution of this service at all levels of health facilities. However, this strategy will only be effective if pregnant women are tested early and provided enough counselling. Objective To assess early uptake of HIV testing and the provision of HIV counselling among pregnant women who attend antenatal care at primary and higher level health facilities. Methods A community based study was conducted among 1108 nursing mothers. Data was collected during interviews using a structured questionnaire focused on socio-economic background, reproductive history, experience with antenatal HIV counselling and testing as well as types of health facility providing the services. Results In all 91.0% of the women interviewed had attended antenatal care and 90.3% had been tested for HIV during their most recent pregnancy. Women who had their first antenatal checkup at primary health facilities were significantly more likely to be tested before 34 weeks of gestation (OR = 43.2, CI: 18.9-98.1). The reported HIV counselling provision was also higher at primary health facilities, where women in comparison with women attending higher level health facilities were nearly three or and four times more likely to receive pre-test (OR = 2.7; CI:2.1-3.5) and post-test counseling (OR = 4.0; CI: 2.3-6.8). Conclusions The results suggest that antenatal HIV counseling and testing can be scaled up to primary heath facilities and that such scaling up may enhance early uptake of testing and provision of counseling.